Invasive fungal rhinosinusitis in Maharaj Nakorn Chiang Mai Hospital - Kannika Roongrotwattanasiri (2018)
Background: Invasive fungal rhinosinusitis, a rare infection, is a life threatening disease. Delay in diagnosis may consequently lead to high morbidity and mortality. Objective: Encourage early detection and proper management of invasive fungal rhinosinusitis. Material and Method: Medical records, radiological, and pathological reports of five patients who were diagnosed as invasive fungal rhinosinusitis were reviewed retrospectively. Results: Four in five cases of invasive fungal rhinosinusitis, confirmed by pathological study, had successful treatment. One patient had intracerebral hemorrhage that may be associated with the disease spreading. Disease extension was evaluated by CT paranasal sinus in all cases, but it usually did not have classic bony erosion. Conclusion: Curing infection, correcting underlying conditions, and working up fungal infection should be carried out as early as possible, because morbidity and mortality depend on disease extension and host status.